Greek writers and philosophers in Philo and Josephus : a study of their secular education and educational ideals - Koskenniemi, Erkki (Studies in Philo of Alexandria, 2019)
In Greek Writers and Philosophers in Philo and Josephus Erkki Koskenniemi investigates how two Jewish writers, Philo and Josephus, quoted, mentioned and referred to Greek writers and philosophers. He asks what this tells us about their Greek education, their contacts with Classical culture in general, and about the societies in which Philo and Josephus lived. Although Philo in Alexandria and Josephus in Jerusalem both had the possibility to acquire a thorough knowledge of Greek language and culture, they show very different attitudes. Philo, who was probably admitted to the gymnasium, often and enthusiastically refers to Greek poets and philosophers. Josephus on the other hand rarely quotes from their works, giving evidence of a more traditionalistic tendencies among Jewish nobility in Jerusalem.